LEGALITY OF REGISTERING INTERRELIGIOUS MARRIAGES IN INDONESIA POST SEMA NUMBER 2 YEAR 2023 - Ahmad Baihaki (International Journal Labs, 2023)
After SEMA No. 2 Year 2023, the opportunity to register interfaith marriages in Indonesia becomes difficult to do. This research aims to find out the extent of the implications of SEMA Law Number 2 Year 2023 on legal certainty regarding the legality of recording interfaith marriages in Indonesia. This research uses normative juridical research methods and is analyzed with philosophical, juridical, and sociological approaches. In conclusion, even though SEMA Number 2 of 2023 has been born, the question of legal certainty of the legality of registering interfaith marriages has not ended because there is still the issue of conflicting norms between the Law and its implementation